Multicolor FISH mapping of the dioecious model plant, Silene latifolia - Lengerova, M; Kejnovsky, E; Hobza, R; Macas, J; Grant, S R; Vyskot, B (TAG. Theoretical and applied genetics. Theoretische und angewandte Genetik, 2004)
Silene latifolia is a key plant model in the study of sex determination and sex chromosome evolution. Current studies have been based on genetic mapping of the sequences linked to sex chromosomes with analysis of their characters and relative positions on the X and Y chromosomes. Until recently, very few DNA sequences have been physically mapped to the sex chromosomes of S. latifolia. We have carried out multicolor fluorescent in situ hybridization (FISH) analysis of S. latifolia chromosomes based on the presence and intensity of FISH signals on individual chromosomes. We have generated new markers by constructing and screening a sample bacterial artificial chromosome (BAC) library for appropriate FISH probes. Five newly isolated BAC clones yielded discrete signals on the chromosomes: two were specific for one autosome pair and three hybridized preferentially to the sex chromosomes. We present the FISH hybridization patterns of these five BAC inserts together with previously described repetitive sequences (X-43.1, 25S rDNA and 5S rDNA) and use them to analyze the S. latifolia karyotype. The autosomes of S. latifolia are difficult to distinguish based on their relative arm lengths. Using one BAC insert and the three repetitive sequences, we have constructed a standard FISH karyotype that can be used to distinguish all autosome pairs. We also analyze the hybridization patterns of these sequences on the sex chromosomes and discuss the utility of the karyotype mapping strategy presented to study sex chromosome evolution and Y chromosome degeneration.
Keywords: Repetitive Sequences, Nucleic Acid; karyotypizace; Silene; mapování chromozomů; Chromosome Mapping; Karyotyping; Chromosomes, Plant; umělé bakteriální chromozomy; chromozomy rostlin; repetitivní sekvence nukleových kyselin; Blotting, Southern; pohlavní chromozomy; Sex Chromosomes; Chromosomes, Artificial, Bacterial; Southernův blotting; hybridizace in situ fluorescenční; genetické markery; In Situ Hybridization, Fluorescence; Genetic Markers